Gradient pyrolysis dual-pore-forming silicon-carbon negative electrode material and preparation method thereof

By employing a gradient pyrolysis dual-pore-forming technology, a bimodal gradient pore structure of macropores and mesopores is formed, which solves the volume expansion problem of silicon-carbon anode materials, improves cycle stability and first-time efficiency, and meets the requirements of high-energy-density lithium-ion batteries.

CN121085244APending Publication Date: 2025-12-09YANGTZE RESOURCES NEW MATERIALS TECH R&D CENT (HUBEI PROVINCE) CO LTD

Patent Information

Application Number
CN202511132203.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing silicon-carbon anode materials suffer from poor cycle stability and rate performance due to volume expansion, making it difficult to meet the development requirements of high-energy-density lithium-ion batteries.

Method used

A gradient pyrolysis dual pore-forming technology is adopted, using ammonium citrate and polylactic acid as pore-forming agents. Through gradient pyrolysis, a bimodal gradient pore structure of macropores and mesopores is formed. Combined with the NH3 reducing atmosphere to suppress silicon oxidation, a core-shell structured silicon-carbon anode material is formed.

Benefits of technology

The capacity retention rate exceeded 91% after 100 electrode cycles, and the initial coulombic efficiency reached 89%, significantly improving cycle stability and interface stability, while reducing production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121085244A_ABST
    Figure CN121085244A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: S1, adding silicon powder, graphite, a carbon source and a pore-forming agent into a solvent to obtain slurry; the pore-forming agent comprises ammonium citrate and polylactic acid; s2, performing spray drying on the slurry to obtain precursor microspheres; s3, the precursor microspheres are subjected to first-stage low-temperature oxidation to form macropores, second-stage medium-temperature melting to form mesopores, third-stage high-temperature carbonization and cooling shaping, the heat preservation temperature of the first-stage low-temperature oxidation is 180-200 DEG C, the heat preservation temperature of the second-stage medium-temperature melting is 340-360 DEG C, the heat preservation temperature of the third-stage high-temperature carbonization is 800-900 DEG C, and the gradient pyrolysis dual-pore-forming silicon-carbon negative electrode material is obtained. Through combined use of ammonium citrate and polylactic acid and control of gradient pyrolysis conditions, synergistic distribution of double-peak gradient pores is formed, and effective improvement of the first effect and the cycle performance can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, specifically to a gradient pyrolysis dual-pore silicon-carbon anode material and its preparation method. Background Technology

[0002] Lithium-ion batteries, as the core of contemporary energy storage technology, directly determine the driving range of electric vehicles and the user experience of consumer electronics through their energy density and cycle life. In the field of anode materials, silicon-based materials, due to their extremely high theoretical specific capacity (approximately 4200 mAh / g, equivalent to more than 10 times that of traditional graphite materials), have become the most promising upgrade direction, expected to drive battery energy density past the technical bottleneck of 300Wh / kg. However, silicon materials experience volume expansion of up to 300% during lithium insertion / extraction, leading to problems such as active particle pulverization, continuous thickening of the solid electrolyte interphase (SEI) film, and damage to the conductive network. These effects collectively cause rapid capacity decay (typically less than 80% retention after 100 cycles) and low initial coulombic efficiency (generally in the range of 70-85%), severely restricting the commercial application of silicon-carbon anodes.

[0003] The industry urgently needs to address the volume effect and interface stability issues of silicon materials while maintaining their high capacity through material innovation and process optimization. To overcome these shortcomings, researchers are exploring solutions primarily from three directions: structural design, composite processes, and interface engineering. For example, Ganzhou Litan New Energy (CN119153670A) proposed a four-level coating structure of "nano-silicon-porous hard carbon-porous metal-carbon coating layer," utilizing a metal framework to enhance mechanical strength. While this approach increases cycle life to over 200 cycles, the introduction of porous metal significantly increases material density, leading to a decrease in specific capacity.

[0004] Liyang Zichen New Materials (CN111640941A) utilizes cyclodextrin and its derivatives as pore-forming agents. The process involves first spray-drying a slurry containing cyclodextrin and its derivatives, followed by decomposition pore formation and secondary coating via chemical vapor deposition (CVD). While cyclodextrin decomposes to produce CO2, forming pores, the concentrated pore size prevents effective buffering of volume expansion, resulting in poor cycling performance (capacity retention of only 80% after 55 cycles). Furthermore, the pore-forming temperature window is narrow (300-400℃), requiring strict matching with the binder decomposition temperature (which must be higher than the pore-forming agent temperature), and CVD has high energy consumption.

[0005] In summary, there is an urgent need to develop a preparation method that can precisely control the pore structure to improve the cycle stability and rate performance of silicon-carbon anode materials, so as to meet the development needs of high-energy-density lithium-ion batteries. Summary of the Invention

[0006] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a gradient pyrolysis dual-pore silicon-carbon anode material and its preparation method, thereby solving the technical problem of poor cycle stability and rate performance of silicon-carbon anode materials due to volume expansion in the prior art.

[0007] To achieve the above-mentioned technical objectives, the technical solution provided by this invention is as follows: In a first aspect, the present invention provides a method for preparing a gradient pyrolysis dual-pore-forming silicon-carbon anode material, comprising the following steps: S1, adding silicon powder, graphite, carbon source and pore-forming agent to a solvent to obtain a slurry; the pore-forming agent includes ammonium citrate and polylactic acid; S2, spray drying the slurry to obtain precursor microspheres; S3, subjecting the precursor microspheres to a first stage of low-temperature oxidation to form macropores, a second stage of medium-temperature melting to form mesopores, and a third stage of high-temperature carbonization and cooling for shaping, wherein the holding temperature for the first stage of low-temperature oxidation is 180-200℃, the holding temperature for the second stage of medium-temperature melting is 340-360℃, and the holding temperature for the third stage of high-temperature carbonization is 800-900℃, thereby obtaining a gradient pyrolysis dual-pore-forming silicon-carbon anode material.

[0008] Secondly, the present invention provides a silicon-carbon anode material prepared by the above-described preparation method.

[0009] Compared with the prior art, the beneficial effects of the present invention include: This invention uses ammonium citrate and polylactic acid as dual pore-forming agents. Through gradient pyrolysis and the synergistic regulation of the dual pore-forming agents, a bimodal gradient pore structure including macropores and mesopores is formed, achieving hierarchical accommodation of silicon expansion stress. This allows the capacity retention rate to reach over 91% after 100 electrode cycles. Simultaneously, the NH3 reducing atmosphere from the decomposition of ammonium citrate inhibits silicon oxidation, reducing irreversible lithium consumption, and achieving an initial coulombic efficiency of ≥89%. Therefore, this invention, through the combined use of ammonium citrate and polylactic acid and the control of gradient pyrolysis conditions, forms a synergistic distribution of bimodal gradient pores, effectively improving both initial efficiency and cycle performance. Attached Figure Description

[0010] Figure 1 This is a SEM image of the carbon anode material of Example 1 of the present invention; Figure 2 This is a SEM image of the carbon anode material of Comparative Example 3 of this invention. Detailed Implementation

[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0012] To address the shortcomings of silicon-carbon anode materials in industrial applications, such as poor cycle stability and rate performance due to volume expansion, this invention provides a gradient pyrolysis dual-pore-forming silicon-carbon anode material and its preparation method. Through the innovative design of gradient pyrolysis synergistic with dual pore-forming agents, the following core objectives are achieved: (1) Graded buffering of volume expansion: A double-peak gradient pore structure (macropores 100–500 nm + mesopores 10–50 nm) is constructed in situ in the carbon layer using a step-type pore-forming mechanism to grade and accommodate silicon expansion stress. (2) Improved first-efficiency and interface stability: The NH3 reducing atmosphere generated by the decomposition of ammonium citrate inhibits silicon surface oxidation, and the gradient carbon layer effectively isolates silicon from electrolyte contact, reducing the continuous growth of the SEI film and reducing the interface impedance by 40% during cycling. (3) Green and low-cost manufacturing: A bio-based biodegradable pore-forming agent is used, leaving no toxic residues and ensuring good environmental friendliness; the process is simplified, reducing energy consumption and production costs, which is 35% lower than the traditional template method that uses sacrificial templates to form regular pores.

[0013] In a first aspect, the present invention provides a method for preparing a gradient pyrolysis dual-pore silicon-carbon anode material, comprising the following steps: S1, silicon powder, graphite, carbon source and pore-forming agent are added to solvent to obtain slurry; the pore-forming agent includes ammonium citrate and polylactic acid; S2, the slurry is spray-dried to obtain precursor microspheres; S3, the precursor microspheres undergo a three-stage process: low-temperature oxidation to form macropores, medium-temperature melting to form mesopores, and high-temperature carbonization and cooling. The holding temperature for the first stage of low-temperature oxidation is 180–200℃, the holding temperature for the second stage of medium-temperature melting is 340–360℃, and the holding temperature for the third stage of high-temperature carbonization is 800–900℃, resulting in a gradient pyrolysis dual-pore-forming silicon-carbon anode material.

[0014] In this invention, the precursor microspheres undergo a first stage of low-temperature oxidation to form macropores. The relatively low temperature at this stage causes the ammonium citrate to decompose, resulting in an explosive gas release and the formation of macropores. The second stage involves medium-temperature melting, which decomposes polylactic acid (PLA). The higher holding temperature in this stage also leads to a small amount of carbonization, transforming the overall structure into a viscoelastic form. The gas produced at this stage balances with the contraction of the carbon skeleton, creating mesopores. The third stage completes the carbonization process. Too low a temperature in any of these three stages will result in incomplete reactions, while too high a temperature in the first two stages will cause both ammonium citrate and PLA to decompose simultaneously.

[0015] Preferably, in step S1, silicon powder and graphite are first mixed and ball-milled to obtain a uniform silicon-graphite mixture, which is then mixed with a carbon source and a pore-forming agent and added to a solvent. The silicon powder used in this invention is micron-sized silicon with a particle size of less than 10 micrometers.

[0016] Further preferably, the silicon powder and graphite are ball-milled to the submicron level (D90 < 5 μm).

[0017] Preferably, in step S1, by mass, the silicon powder comprises 800-1000 parts, graphite 190-210 parts, carbon source 160-240 parts, ammonium citrate 40-80 parts, and polylactic acid 60-100 parts.

[0018] Preferably, in step S1, the solvent is an aqueous solution of isopropanol; more preferably, the volume ratio of deionized water to isopropanol is 3:1.

[0019] Preferably, in step S1, the solid content of the slurry is 25-35 wt%, more preferably 28-32 wt%.

[0020] Preferably, in step S2, the spray drying conditions include: inlet temperature 150-210℃, outlet temperature 70-120℃, atomization pressure 0.3-0.4MPa, and feed rate 10-20mL / min.

[0021] Preferably, in step S2, the precursor microspheres have a particle size of 20–50 μm and a water content of <2 wt%.

[0022] Preferably, in step S3, a low-temperature oxidation stage involves raising the temperature from room temperature to 180–200°C at a rate of 1–5°C / min in an air atmosphere and holding it at that temperature for 1–2 hours.

[0023] Ammonium citrate decomposes at 180-200°C in the presence of oxygen. Therefore, the low-temperature oxidation process of this invention uses an air atmosphere to lower the decomposition temperature of ammonium citrate and to prevent polylactic acid from softening and deforming prematurely. Polylactic acid softens and enters a high-melting state below 200°C, but the molecular chains do not break. At this time, the pores caused by ammonium citrate will not lead to a collective collapse.

[0024] More preferably, the air flow rate is 75–200 mL / min.

[0025] Preferably, in step S3, the second-stage medium-temperature melting is carried out under a protective atmosphere, with the temperature increased from 180-200°C to 340-360°C at a heating rate of 1-5°C / min and held for 2-3 hours.

[0026] Further preferably, the protective atmosphere for the two-stage intermediate-temperature melting includes argon gas with a flow rate of 100–250 mL / min.

[0027] Preferably, in step S3, the three-stage high-temperature carbonization is carried out under a protective atmosphere, with the temperature increased from 340-360°C to 800-900°C at a rate of 3-5°C / min and held for 3-4 hours.

[0028] Further preferred, the protective atmosphere for the three-stage high-temperature carbonization includes argon gas with a flow rate of 75–200 mL / min.

[0029] Preferably, in step S3, the pore size of the macropores is 100-500 nm, and the pore size of the mesopores is 10-50 nm; the volume ratio of macropores is 60-70%, and the volume ratio of mesopores is 30-40%.

[0030] Preferably, in step S3, the cooling is performed in the furnace under a protective atmosphere.

[0031] Further preferably, the cooling protective atmosphere comprises argon gas at a flow rate of 50 mL / min.

[0032] Secondly, the present invention provides a silicon-carbon anode material prepared by the above-described preparation method.

[0033] Preferably, the silicon-carbon anode material is a microsphere formed by the aggregation of core-shell structured particles. In the core-shell structured particles, the shell layer is a carbon layer, the core is a silicon-graphite mixture, the interface between the silicon-graphite mixture and the carbon layer has macropores, and the carbon layer has mesopores.

[0034] The main working mechanism of the gradient pyrolysis four-stage process of this invention: Stage 1: Low-temperature oxidation to create macropores (25℃ → 200℃), the main reaction mechanism is:

[0035] The NH3 / CO2 gas released by the oxidation and decomposition of ammonium citrate forms macropores of 100–500 nm within the microspheres, while a passivation layer (SiO2) is formed on the surface of the air-oxidized silicon. x (x<0.5), and because the NH3 reducing atmosphere inhibits silicon oxidation, the surface SiO x The layer thickness is relatively small (<1 nm).

[0036] Phase Two: Mesoporous Formation via Intermediate-Temperature Melting (200℃ → 350℃), the main reaction mechanism being PLA melt decomposition:

[0037] Molten PLA encapsulates silicon particles, decomposes to generate gas and forms 10-50 nm mesopores, while the carbon source (taking sucrose as an example) is pre-carbonized to generate an amorphous carbon skeleton.

[0038] Stage 3: High-temperature deep carbonization (350℃ → 800℃), the reaction mechanism mainly includes: (1) Sucrose carbonization reaction:

[0039] (2) Graphitization of carbon layers: ID / IG value decreased to 0.80-0.85; (3) Nitrogen doping and solidification: nitrogen-containing free radicals derived from ammonium citrate are embedded in the carbon layer, forming pyridine nitrogen functional groups on the surface.

[0040] Phase 4: This invention adopts furnace cooling and slow cooling shaping (800℃ → 30℃) to avoid thermal stress causing pore collapse and to retain the gradient pore structure.

[0041] The present invention has the following main advantages: (1) Improved cycle stability: The present invention uses a dual-pore-forming coating structure to form a synergistic distribution of bimodal gradient pores. The bimodal gradient pores hierarchically accommodate silicon expansion stress, so that the capacity retention rate of the electrode after 100 cycles is >91% (1C, 25℃), and the cycle stability is good, indicating that the volume expansion rate is low under full lithium insertion state.

[0042] (2) Integrity and functionalized interface of carbon layer coating: The carbon layer is an amorphous carbon coating layer with a thickness of 20-50 nm and an integrity coating rate >95%. Inner interface (silicon-carbon layer): There is a 5-10 nm transition region between the carbon layer and silicon particles. Outer interface (carbon layer-electrolyte): The carbon layer surface is enriched with pyridine nitrogen functional groups, which can enhance the wettability of the electrolyte (contact angle <15°). Conductive network: The graphitization degree of the carbon layer ID / IG = 0.80-0.85, and the conductivity >10 -2 S / cm.

[0043] (3) Confinement and stress release structure of silicon particles: Silicon distribution morphology: Micron-sized silicon particles (below 5μm) are divided and wrapped by flake graphite; the carbon coating integrity of single silicon particles is >90%. The distance between macropores and silicon particles is ≤50 nm, ensuring that expansion stress is preferentially released to the pores; mesopores form a "micro-spring" structure in the carbon layer.

[0044] (4) Significantly improves first-efficiency and interfacial kinetics: The NH3 reducing atmosphere from the decomposition of ammonium citrate inhibits silicon oxidation (surface SiO2). x With a layer thickness of <1 nm, irreversible lithium consumption is reduced, and the initial coulombic efficiency is ≥89% (0.1C), which is 7-11% higher than that of traditional solutions (78-82%).

[0045] (5) Breakthrough in process efficiency: By eliminating steps such as HF etching, production costs are reduced by about 35%. The total time for gradient pyrolysis process is 6-9 hours, which is about 50% more energy-efficient than vapor deposition.

[0046] The present invention will be further described in detail below through specific embodiments.

[0047] Example 1 A method for preparing a gradient pyrolysis dual-pore silicon-carbon anode material includes the following steps: S1, Pretreatment: Place 1000g of silicon powder and 200g of graphite in a horizontal ball mill jar and ball mill for 18 hours to obtain a uniform silicon-graphite mixture. Add 160g of sucrose, 50g of ammonium citrate, and 75g of polylactic acid, and then place them together in a mixing tank. Add a mixture of 30L of deionized water and 10L of isopropanol to the tank and stir and disperse overnight for 12 hours.

[0048] S2, Spray Drying: Adjust equipment parameters: inlet temperature 180±5℃, outlet temperature 95±5℃; atomization pressure 0.3 MPa, feed rate 10 mL / min. The precursor solution is passed into the spray drying equipment for granulation to obtain precursor microspheres.

[0049] S3. The precursor microspheres were placed in a rotating tube furnace for gradient pyrolysis. Stage 1: Heating rate 2℃ / min, holding at 200℃ for 1 h, air atmosphere (flow rate 100 mL / min). Stage 2: Heating rate 1℃ / min; holding at 350℃ for 2 h, argon atmosphere (flow rate 200 mL / min). Stage 3: Heating rate 5℃ / min, holding at 800℃ for 3 h, argon atmosphere (flow rate 100 mL / min). Stage 4: Furnace cooling (approximately 2℃ / min), argon atmosphere (flow rate 50 mL / min); silicon-carbon anode material was obtained.

[0050] Example 2 A method for preparing a gradient pyrolysis dual-pore silicon-carbon anode material includes the following steps: S1, Pretreatment: Place 800g of silicon powder and 200g of graphite in a horizontal ball mill jar and ball mill for 18 hours to obtain a uniform silicon-graphite mixture. Add 200g of sucrose, 40g of ammonium citrate, and 60g of polylactic acid, and then place them together in a mixing tank. Add a mixture of 40L of deionized water and 50L of isopropanol to the tank and stir and disperse overnight for 12 hours.

[0051] S2, Spray Drying: Adjust equipment parameters: inlet temperature 200±5℃, outlet temperature 110±5℃; atomization pressure 0.4 MPa, feed rate 20 mL / min. The precursor solution is passed into the spray drying equipment for granulation to obtain precursor microspheres.

[0052] S3. The precursor microspheres were placed in a rotating tube furnace for gradient pyrolysis. Stage 1: Heating rate 5℃ / min, holding at 200℃ for 2 h, air atmosphere (flow rate 75 mL / min). Stage 2: Heating rate 5℃ / min; holding at 350℃ for 3 h, argon atmosphere (flow rate 100 mL / min). Stage 3: Heating rate 3℃ / min, holding at 800℃ for 4 h, argon atmosphere (flow rate 75 mL / min). Stage 4: Furnace cooling (approximately 2℃ / min), argon atmosphere (flow rate 50 mL / min); silicon-carbon anode material was obtained.

[0053] Example 3 A method for preparing a gradient pyrolysis dual-pore silicon-carbon anode material includes the following steps: S1, Pretreatment: Place 1000g of silicon powder and 200g of graphite in a horizontal ball mill jar and ball mill for 24 hours to obtain a uniform silicon-graphite mixture. Add 240g of sucrose, 75g of ammonium citrate, and 100g of polylactic acid, and then place them together in a mixing tank. Add a mixture of 25L of deionized water and 15L of isopropanol to the tank and stir and disperse overnight for 12 hours.

[0054] S2, Spray Drying: Adjust equipment parameters: inlet temperature 160±5℃, outlet temperature 80±5℃; atomization pressure 0.3 MPa, feed rate 15 mL / min. The precursor solution is passed into the spray drying equipment for granulation to obtain precursor microspheres.

[0055] S3. The precursor microspheres were placed in a rotating tube furnace for gradient pyrolysis. Stage 1: Heating rate 1℃ / min, holding at 200℃ for 2 h, air atmosphere (flow rate 200 mL / min). Stage 2: Heating rate 3℃ / min; holding at 350℃ for 3 h, argon atmosphere (flow rate 250 mL / min). Stage 3: Heating rate 5℃ / min, holding at 800℃ for 3 h, argon atmosphere (flow rate 200 mL / min). Stage 4: Furnace cooling (approximately 2℃ / min), argon atmosphere (flow rate 50 mL / min); silicon-carbon anode material was obtained.

[0056] Comparative Example 1 Compared with Example 1, the only difference is that ammonium citrate is not added in step S1, while the other steps and conditions are the same as in Example 1.

[0057] Comparative Example 2 Compared with Example 1, the only difference is that polylactic acid is not added in step S1, while the other steps and conditions are the same as in Example 1.

[0058] Comparative Example 3 Compared with Example 1, the only difference is that 150g of polylactic acid is added in step S1, while the other steps and conditions are the same as in Example 1.

[0059] Comparative Example 4 Compared with Example 1, the only difference is that in step S3, stage one is changed from room temperature to 250°C and kept at that temperature for 2 hours. The other steps and conditions are the same as in Example 1.

[0060] Electrochemical testing methods 1. Method for testing coulomb efficiency in the first week: Test setup: CR2032 coin cell (negative electrode: silicon-carbon negative electrode material to be tested; positive electrode: lithium metal sheet; electrolyte: 1M LiPF6 in EC / DEC=1:1).

[0061] Test procedure: ① Discharge at a constant current of 0.1C (1C=2000 mA / g) to 0.01V (vs. Li⁺ / Li), then switch to constant voltage until the current ≤0.005C; ② After standing for 5 min, charge at a constant current of 0.1C to 1.5V; ③ First-cycle coulombic efficiency = (discharge capacity / charge capacity) × 100%.

[0062] Standard: GB / T 37201-2018 "Test Methods for Electrochemical Performance of Anode Materials for Lithium-ion Batteries".

[0063] 2. Capacity retention rate test method: The capacity retention rate is tested using a coin cell half-cell under the condition of 1C cycling 100 times.

[0064] (1) Battery assembly Negative electrode preparation: Active material (silicon-carbon negative electrode material to be tested): Conductive agent (Super P): Binder (PAA) = 8:1:1 coated on copper foil (area density ≈ 2.5 mg / cm²), vacuum dried at 120℃ for 12 h; Counter electrode: 16 mm diameter lithium metal sheet (thickness 0.6 mm); Electrolyte: 1 M LiPF6 in EC / DEC + 10 wt% FEC; Separator: Celgard 2400; Battery model: CR2032 (assembled in a glove box with dew point ≤ -40℃).

[0065] (2) Testing process Activation cycle (0.1C, 1C=2000 mA / g): ① Discharge: 0.1C constant current (100 mA / g) → 0.01 V → constant voltage until current ≤0.005C; ② Charge: 0.1C constant current → 1.5 V; repeat 5 times (to eliminate the irreversible effect of the initial SEI formation).

[0066] Cyclic testing: 1C rate cycling (2000 mA / g), constant current charge and discharge: discharge to 0.01V → charge to 1.5V (no constant voltage stage); 300 cycles, temperature 25±1℃.

[0067] Capacity retention rate = (Discharge capacity at 100th cycle / Discharge capacity at 6th cycle) × 100%.

[0068] 3. Conductivity testing methods: Equipment: Four-probe resistance meter (Loresta-GX MCP-T700); Method: The coating material is scraped off the silicon core and pressed into a 10mm diameter disc (pressure 10 MPa); The resistivity ρ is directly measured using the four-probe method, and the electronic conductivity = 1 / ρ.

[0069] Performance testing (1) The scanning electron microscope image of the silicon-carbon anode material obtained in Example 1 is shown below. Figure 1 As shown, it exhibits a bimodal gradient porosity distribution structure. The internal state of the sphere can be seen within the boxed area of ​​the figure. The macroporous structure, with a pore size ranging from 100 to 500 nm, is an irregular ellipsoid, concentrated at the interface between silicon particles and the carbon layer. This directly buffers the expansion stress from silicon lithium intercalation, reducing the volume change rate to <8.5%. The mesoporous structure, with a pore size ranging from 10 to 50 nm, forms an interconnected network that penetrates the carbon layer, providing rapid ion transport channels and increasing the lithium-ion diffusion coefficient to 10. -11 cm 2 / s. Macropores account for 60-70% of the volume, while mesopores account for 30-40%, forming a hierarchical system of "macropores absorbing energy and mesopores conducting ions".

[0070] like Figure 2 As shown, the silicon-carbon anode material obtained in Comparative Example 3 was observed by electron microscopy and found that it did not granulate into spheres, which may be due to the decomposition of excessive polylactic acid leading to the rupture of microspheres.

[0071] (2) The silicon-carbon anode materials of Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the results are shown in Table 1 below.

[0072] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-3

[0073] As shown in Table 1, compared with Example 1, Comparative Example 1 removed ammonium citrate, Comparative Example 2 removed polylactic acid, and Comparative Example 3 added excessive polylactic acid. All of these resulted in a decrease in the performance of the obtained silicon-carbon anode material. This indicates that the present invention, through the combined use of ammonium citrate and polylactic acid and the control of gradient pyrolysis conditions, forms a synergistic distribution of bimodal gradient pores, which can effectively improve the first-efficiency and cycle performance.

[0074] In Comparative Example 4, the insulation temperature in Stage 1 was increased to 250℃. At this temperature, both ammonium citrate and polylactic acid reacted, making the structure relatively fragile and resulting in a significant decrease in cycle stability.

[0075] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a gradient pyrolysis dual-pore silicon-carbon anode material, characterized in that, Includes the following steps: S1, silicon powder, graphite, carbon source and pore-forming agent are added to solvent to obtain slurry; the pore-forming agent includes ammonium citrate and polylactic acid; S2, the slurry is spray-dried to obtain precursor microspheres; S3, the precursor microspheres undergo a three-stage process: low-temperature oxidation to form macropores, medium-temperature melting to form mesopores, and high-temperature carbonization and cooling. The holding temperature for the first stage of low-temperature oxidation is 180–200℃, the holding temperature for the second stage of medium-temperature melting is 340–360℃, and the holding temperature for the third stage of high-temperature carbonization is 800–900℃, resulting in a gradient pyrolysis dual-pore-forming silicon-carbon anode material.

2. The method for preparing gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S1, the silicon powder and graphite are first mixed and ball-milled to obtain a uniform silicon-graphite mixture, which is then mixed with a carbon source and a pore-forming agent and added to a solvent.

3. The method for preparing the gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S1, by mass, the silicon powder is 800-1000 parts, graphite is 190-210 parts, carbon source is 160-240 parts, ammonium citrate is 40-80 parts and polylactic acid is 60-100 parts.

4. The method for preparing the gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S1, the solvent is an aqueous solution of isopropanol; and / or, The solid content of the slurry is 25-35 wt%.

5. The method for preparing the gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S2, the spray drying conditions include: inlet temperature 150–210°C, outlet temperature 70–120°C, atomization pressure 0.3–0.4 MPa, and feed rate 10–20 mL / min; and / or, The precursor microspheres have a particle size of 20–50 μm and a water content of <2 wt%.

6. The method for preparing the gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S3, the first stage of low-temperature oxidation is carried out in an air atmosphere, with the temperature increased from room temperature to 180-200°C at a rate of 1-5°C / min and held at that temperature for 1-2 hours.

7. The method for preparing the gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S3, the two-stage medium-temperature melting is carried out under a protective atmosphere, with the temperature increased from 180-200°C to 340-360°C at a heating rate of 1-5°C / min and held for 2-3 hours.

8. The method for preparing gradient pyrolysis dual-pore silicon-carbon anode material according to claim 1, characterized in that, In step S3, the three-stage high-temperature carbonization is carried out under a protective atmosphere, with the temperature increased from 340-360°C to 800-900°C at a rate of 3-5°C / min and held for 3-4 hours.

9. The silicon-carbon anode material prepared by the preparation method according to any one of claims 1-8.

10. The silicon-carbon anode material according to claim 9, characterized in that, The silicon-carbon anode material is a microsphere formed by the aggregation of core-shell structured particles; in the core-shell structured particles, the shell layer is a carbon layer, the core is a silicon-graphite mixture, the interface between the silicon-graphite mixture and the carbon layer has macropores, and the carbon layer has mesopores. The macropores have a diameter of 100–500 nm, and the mesopores have a diameter of 10–50 nm; the volume ratio of the macropores is 60–70%, and the volume ratio of the mesopores is 30–40%.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material taking cyclodextrin and derivatives thereof as pore-forming agent and preparation method

    CN111640941A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN119153670A

Cited By

  • Spherical artificial graphite composite particle and spray drying preparation method and application thereof

    CN122000330A